Bidder cash reserve effect under the precautionary motive: Evidence from UK - Ning Gao; Abdulkadir Mohamed (The University of Manchester, Manchester Business School, 2011)
Cash-rich bidders in UK have better announcement abnormal returns than cash-poor ones during 1984-2007, contrasting previous findings in the US. The positive cash reserve effect is mainly from bidders of high long-run growth or those with non-trivial institutional holdings. Moreover, cash-rich bidders' post-acquisition operating performance is positively related to bidder cash reserve and institutional holdings. Our results suggest the precautionary motive underlies bidder cash reserve effects. Specifically, cash-rich bidders are better positioned to capture growth opportunities arising from acquisitions. Our results also suggest that strong shareholder power is necessary to ensure cash reserved in the interests of shareholders.
Keywords: G34; D82; 330; precuationary motive of cash reserve; excess cash reserve; acquisition; institutional holding; shareholder power; announcement effect; Übernahme; Betriebliche Liquidität; Ankündigungseffekt; Unternehmenserfolg; Großbritannien